2014
DOI: 10.1371/journal.pone.0115241
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Evolutionary Significance of Human MicroRNA Seed Region Mutations

Abstract: MicroRNAs have emerged in recent years as important regulators of cell function in both normal and diseased cells. MiRNAs coordinately regulate large suites of target genes by mRNA degradation and/or translational inhibition. The mRNA target specificities of miRNAs in animals are primarily encoded within a 7 nt “seed region” mapping to positions 2–8 at the molecule's 5′ end. We here combine computational analyses with experimental studies to explore the functional significance of sequence variation within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 22 publications
2
25
0
1
Order By: Relevance
“…There is a high functional cost of even single nucleotide changes within seed regions, which is consistent with their high sequence conservation among miRNA families both within and between species and suggests processes that may underlie the evolution of miRNA regulatory control (Hill et al, 2014). The target specificity determined by the seed has evolutionary and biological implications because single nucleotide polymorphisms in canonical miRNA binding sites would affect miRNA-mediated regulations, a notion supported also by experimental data (Afonso-Grunz and Muller, 2015;Vosa et al, 2015).The canonical 7nt seed can be divided into several types (Ellwanger et al, 2011).…”
Section: Seed-involving Interactionssupporting
confidence: 52%
“…There is a high functional cost of even single nucleotide changes within seed regions, which is consistent with their high sequence conservation among miRNA families both within and between species and suggests processes that may underlie the evolution of miRNA regulatory control (Hill et al, 2014). The target specificity determined by the seed has evolutionary and biological implications because single nucleotide polymorphisms in canonical miRNA binding sites would affect miRNA-mediated regulations, a notion supported also by experimental data (Afonso-Grunz and Muller, 2015;Vosa et al, 2015).The canonical 7nt seed can be divided into several types (Ellwanger et al, 2011).…”
Section: Seed-involving Interactionssupporting
confidence: 52%
“…The mutation profile of the mature sequences confirmed the pattern found by Wheeler et al (154; see also 55, 58), as the same two regions of the mature sequence - the seed region (positions 2-8) and the 3′ complementarity region (positions 13-16) - showed few instances of nucleotide substitutions compared with positions 1, 10-12, and 17-22 (Figure 6a, bottom). The frequency of substitutions in the seed region was effectively zero, with only ten changes seen in the 29,007 positions analyzed, confirming the functional importance of this region of the molecule (11, 60, 69, 152), and calling into question the long-term evolutionary importance of non-canonical interactions between miRNAs and target mRNAs (65, 134). …”
Section: Nucleotide Substitution Rates Of Mature Versus Star Sequencesmentioning
confidence: 69%
“…Therefore, investigation of the relationship between genetic variants in noncoding genomic regions and gene function may help to improve our knowledge about the associations between genotypes and phenotypes. Previous studies in miRNA variation reported a high conservation of human miRNAs [Saunders et al., ; Quach et al., ]; and although several examples showing the association of miRNA genetic variants with disease have already been described [Jazdzewski et al., ; Hoffman et al., ; Jazdzewski et al., ; Xu et al., ; Xu et al., ; Lopez‐Valenzuela et al., ; Soldà et al., ; Chen et al., ; Fu et al., ; Hrdlickova et al., ; Wan et al., ; Xu et al., ; Zhou et al., ], there is still little information on the functional consequences that these genetic changes may have [Duan et al., ; Jazdzewski et al., ; Jazdzewski et al., ; Lopez‐Valenzuela et al., ; Ghanbari et al., ; Hill et al., ]. Here, we analyzed global genetic variation in miRNA regions among human populations and look for the functional differences between allele variants of three common miRNA SNVs that had repeatedly been associated with different types of cancer.…”
Section: Discussionmentioning
confidence: 99%